2016
DOI: 10.1080/03019233.2016.1241518
|View full text |Cite
|
Sign up to set email alerts
|

Inclusions modification in heat resistant steel containing rare earth elements

Abstract: Based on the thermodynamic assessment of inclusions evolution, the modification experiments of inclusions containing rare earths were carried out in the Si-Mo furnace from 1600°C to 1500°C. The pure Si and Si-Al alloy were chosen as deoxidants under low and high initial oxygen content, respectively. The field emission scanning electron microscope (FE-SEM) and energy dispersive spectrometer (EDS) were employed to analyse the morphology and chemical compositions of inclusions in the samples. The spherical liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…According to the results, for experimental steels with different Ce content, the Δ G of rare earth oxides, rare earth sulphides and rare earth sulphur oxides were negative, indicating that Ce element can combine with S and O element to form inclusions in molten steel. The result was consistent with other researchers [9,19]. However, the Δ G of rare earth carbides and rare earth phosphides were positive, indicating those inclusions were not formed in molten steel.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…According to the results, for experimental steels with different Ce content, the Δ G of rare earth oxides, rare earth sulphides and rare earth sulphur oxides were negative, indicating that Ce element can combine with S and O element to form inclusions in molten steel. The result was consistent with other researchers [9,19]. However, the Δ G of rare earth carbides and rare earth phosphides were positive, indicating those inclusions were not formed in molten steel.…”
Section: Resultssupporting
confidence: 92%
“…In the past, many studies have been carried out to understand rare earth sulphides, rare earth oxides, and rare earth phosphides [7][8][9]. However, these reports do not seem to give more attention to the morphology, distribution, and precipitation mechanism of rare earth carbides.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12–17 ] Besides, the microstructure and property of steels could be significantly improved by an appropriate addition of rare earth elements. [ 18–23 ] Li et al [ 24 ] found that the evolution path of a Si‐Al killed 253 MA steel was Si–Al–O→Ce 2 O 3 (Ce 2 O 2 S) →Ce–Si–Al–O, which was in liquid state under 1773 K. Ren et al [ 25 ] found that when the cerium content in an aluminum‐killed steel increased from 0 to 280 ppm, the modification sequence of inclusions was Al 2 O 3 → CeAlO 3 → Ce 2 O 2 S → Ce 2 O 2 S and CeS. Li et al [ 26 ] found that the undercooling degree of a 1045 steel could be reduced by cerium‐containing inclusions, and the equiaxed grain zone in the cast steel was enlarged after additions of rare earth elements.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Besides, the microstructure and property of steels could be significantly improved by an appropriate addition of rare earth elements. [18][19][20][21][22][23] Li et al [24] found that the evolution path of a Si-Al killed 253 MA steel was Si-Al-O!Ce 2 O 3 (Ce 2 O 2 S) !Ce-Si-Al-O, which was in liquid state under 1773 K. Ren et al [25] found that when the cerium content in an aluminum-killed steel increased from 0 to 280 ppm, the modification sequence of inclusions was Al 2 O 3 ! CeAlO 3 !…”
mentioning
confidence: 99%
“…[4][5][6][7][8] Particularly, large and long MnS inclusions precipitated during heat treatment after rolling of the steel and have a detrimental effect on the strength and corrosion resistance of heavy rail steels. [9][10][11][12][13] Many studies were reported to control large-sized MnS inclusions according to the characteristic and source of MnS in the steel, such as slag refining, [14,15] calcium/magnesium addition, [16][17][18][19] zirconium/cerium addition, [20][21][22] heat treatment process, [23,24] and heterogeneous nucleation improvement. [25][26][27] Oikawa et al [28,29] studied the effect of Ti addition on the formation and distribution of MnS inclusions in Fe-0.1%C-1%Mn-0.02%S steels during solidification.…”
mentioning
confidence: 99%